ANALISIS KESTABILAN LERENG UNTUK OPTIMASI ENDAPAN BA-TUBARA DI AREA LOWWALL PIT XYZ PT. KIDECO JAYA AGUNG KECAMATAN BATU SOPANG KABUPATEN PASER PROVINSI KALIMANTAN TIMUR - Trynovianti Putri Malik; Supandi; Novandri Kusuma Wardana (Retii, 2021)
Abstract Pit XYZ is one of the Pits at Pt. Kideco Jaya Agung, where there is a lowwall area that has experienced landslides and as the area still has coal deposits, coal sediment optimization will be carried out. In the optimization of coal deposits, it is necessary to do a back analysis to determine the value of geotechnical parameters (cohesion and inner friction angle) so that the value of the safety factor on the actual slope is known and it can provide recommendations for safe and stable geometric designs. This research is conducted using quantitative methods. In the data processing, a back analysis is performed on each section. The analysis of safety factors and recommendations for slope geometry is carried out using the Morgenstern-Price method. The results show the actual slope stability value for section A with FK = 1,090 and section B with FK = 1,082. After obtaining the FK and PK values on the actual slopes, an optimization design was made for each section with FK = 1,025 and FK = 1,032 for section A and B respectively. This optimization design does not meet the criteria so the researcher makes geometric design options for each section, section A has a value of FK = 1.399% and section B has a value of FK = 1.301. Key words: safety factor, optimum geometric design